THE INFLUENCE OF ORGANISATIONAL PRACTICES AND ROUTINES (SERVICE ORIENTED BUSINESS STRATEGY AND SERVICE TRAINING TO ORGANISATIONAL PERFORMANCE DRIVERS SERVICE ORIENTATION AND INTENTION TO LEAVE THROUGH EMPLOYEE ATTITUDES JOB SATISFACTION AND AFFECTIVE COMMITMENT IN FIVE-STARS HOTEL IN JAKARTA - Agung Iman Sudrajat (Universitas Trisakti, 2010)
The background of this research was managers need to determine how organisational practices and routines influence service staff attitudes and behaviours and how the latter set affects organisational performance drivers. Service organisations can enhance their performance by putting in place strategies and practices that strengthen the service-oriented behaviours of theiremployees and reduce their intention to leave the organisation. The objective of this reseach was to investigate the effect of organisational practices and rotines toward organisational performance mediated by employee attitudes in hotels. The design of this reseach applies to five hotels (five stars) in Jakarta and the questionnaires were spreaded away to 181 respondent/employees by using convenience sampling. The result of this reseach conclude that: a) Service oriented businessstrategy has a significant and substantial influence on service orientation. b)Service training did not have a significant dirrect effect on service orientation. c) Service training significanlyinfluenced job satisfaction. d) Job satisfaction has a significant influence on service orientation. e) Job satisfaction has a significant influence on affective commitment. f) Affective commitment has a significant influence on intention to leave. g) Affective commitment has asignificant influence on service orientation